Future changes in rice cultivation in the central zone of Kerala - Riya K. R.; B. Ajithkumar (Annals of Agricultural Research, 2023)
Climate change poses significant challenges to agriculture, particularly in developing countries with tropical and subtropical regions. Rice, as a staple food crop for a large portion of the global population, is highly susceptible to the impacts of climate change. This study focuses on analyzing the potential effects of climate change on rice cultivation in the central zone of Kerala, India, using the CERES-Rice model within the Decision Support System for Agrotechnology Transfer (DSSAT) software. The research examines two rice varieties, Jyothi (short duration) and Jaya (medium duration), under different climate change scenarios for the base period, mid-century, and end of the century. The findings reveal a decline in rice production for both varieties, with greater yield reductions in early plantings compared to late plantings in future simulations. The decrease in yield can be attributed to rising temperatures, which hinder pollen germination, accelerate leaf senescence, and reduce photosynthetic rates. Additionally, changes in rainfall patterns, particularly excessive rainfall during the flowering period, may influence yield variations between early and late plantings. These results emphasize the need for adaptation strategies, such as shifting planting dates, to optimize rice production in the face of changing climatic conditions. Further research and sustainable agricultural practices are crucial to ensure food security and mitigate the adverse impacts of climate change on rice cultivation.